Hardness Analysis of Bearing on Heat Treatment Process - Kisman H Mahmud; Sri Anastasia Yudistirani; Ery Diniardi; A I Ramadhan (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2020)
Bearing is a mechanical element that resembles a loaded shaft, so that rotation or back and forth motion can be smooth, safe and long lasting. Bearings should be sturdy and durable to allow the shaft and other machine elements to work properly. If the bearing is not working properly then the performance of the whole system will decline or not work properly. For this reason, materials from high-carbon steel bearings should be durable and durable. To obtain the desired properties of the metal, the Heat Treatment process, especially the outer and inner ring, is used. Hardness testing of the outer and inner ring of the bearing is performed after the Heat Treatment process. Testing the violence using the Digital Rockwell Hardness Tester, the value of the violence can be read directly on the scale of the tool. The Heat Treatment process of the outer and inner ring of the bearing can produce the mechanical properties that the manufacturer wants, namely Rockwell hardness 62-64 HRC. If the result of the hardness test is in accordance with the factory standard, then the outer and inner ring meet the manufacturer's quality requirements.